Farmers Perception And Sustainability Strategy On Agricultural Development Program In Rural - Oktarina, Selly; Malini, Henny (Jurnal Social Economic of Agriculture, 2021)
This article aimed to describe the agricultural development program, to measure the farmers' perception of the agricultural development program, and to describe the strategy of the agricultural development program. This research was conducted in the Indralaya district of Muara Penimbung village Ogan Ilir Regency Indonesia by used a survey method. Involving 30 farmers as the samples by simple random sampling. Data processing is performed by scores and described in a descriptive. The results showed that the agricultural development program implemented were sufficiently varied to improve the well-being of farmers. These programs were Field School of Integrated Crop Management (SLPTT) and Village Irrigation Network. The farmers have good perceptions of the implementation of the agricultural development program. The socialization, implementation, and evaluation stage of the program is implemented involving key informants and a Field Agricultural Extension (PPL). The strategy of the agricultural development program is to conduct the internal assessment, group farmers together, rotate groups on the program and create high-quality, location-specific products.Keywords: agricultural, development, implementation, perception, strategy.